Design and Analysis of Modified Sierpinski Gasket Fractal Antenna - Mehak; Shashi B, Rana; Bhomia, Yogesh (International Journal of Computer Sciences and Engineering, 2025)
A Modified Sierpinski Fractal patch antenna has been designed and analyzed in this paper. As research in the field of antenna design has already established, therefore it is exceptional that a novel approach is used over conventional antenna design methods to optimize the existing sierpinski fractal antenna. This fractal structure is implemented on square and several iterations are applied on initial shape. The space filling and self-similarity property are used to design above said antenna. The proposed fractal antenna is designed on RT-DUROID substrate of thickness 1.6mm and relative permittivity of 2.2 and mounted above the ground plane at a height of 6mm using IE3D simulation software. Here, microstrip line feed is used to excite the antenna. Performance has been analyzed in terms of return loss, VSWR, input impedance, gain, and bandwidth in the 1 GHz to 5 GHz frequency range. The proposed antenna provides an impedance bandwidth of 56 % and high gain around the resonant frequency of 0.55 GHz .This antenna design can be used in Ground Penetration Radar (GPR), which is found to be suitable for land mine detection.